A Pragmatic Analisys on Verbal Offers Used by Cloth Sellers in Pasar Traditional Modern (PTM) Bengkulu - Detti Lismayanti (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2013)
The problems in this research are: (1)What authenticevaluation models which applied by teachers of English at MAN 2 Kota Bengkulu, (2) What are the steps that isused by teachers of English at MAN 2 Kota Bengkulu? (3) What are the constraints that faced by teachers ofEnglish at MAN 2 Kota Bengkulu? (4) What are the efforts that is made by teachers of English at man 2 KotaBengkulu? (5) What is the need of English teachers in developing authentic evaluation instruments at MAN 2Kota Bengkulu? The sample of this research is census sample, that is all individual in the population are chosento be sample. Census is taken because the number of population is small. The are 4 teachers to be the sample inthis research. Based on the analysis English teachers had problems in applying the authentic evaluation. Theteachers had done all of the instuments of authentic evaluation to the students. The constraints are the limit oftime, facilities and infrastructures, the difficulties in appliying authentic evaluation of specific competency, haveproblems of about the students. The teachers of English at MAN 2 Kota Bengkulu